Power relations and contrasting conceptions of evidence in patient-involvement processes used to inform health funding decisions in Australia. (June 2015) - Lopes, Edilene; Carter, Drew; Street, Jackie
Abstract: We collected and analysed views of key stakeholders on the processes used to involve patient organisations in health care funding decision making in Australia. We conducted 12 semi-structured interviews with patient organisation representatives and members of Advisory Committees that provide advice to the Australian Department of Health and employ Health Technology Assessment (HTA) as an evaluation framework. Using two theoretical frameworks, we analysed structural and contextual elements pertaining to the involvement processes. The findings reported in this article relate to interviewees' perspectives on contextual elements, analysed using a Foucauldian lens. These elements include: the perspectives of marginalised voices; the diversity of views on what ought to be considered valid evidence in a HTA setting; and the relationships between stakeholders, along with how these relationships impact on involvement processes and the outcomes of those processes. The findings demonstrate that the involvement processes currently used are deemed inadequate by both patient organisation representatives and Advisory Committee members, but for different reasons connected to how different stakeholders conceptualise evidence. Advisory Committee members viewed evidence as encompassing clinical outcomes and patient preferences, whereas patient organisation representatives tended to view evidence as encompassing aspects not directly related to a disease entity, such as the social and emotional aspects of patients' experiences in living with illness. Patient organisation representatives reported interacting with other stakeholders (especially industry) to increase the influence of their conception of evidence on decision making. The use of this strategy by interviewees illustrates how power struggles occur in government decision-making processes which involve both medical expertise and patients' accounts. Such struggles, and the power differentials they reflect, need to be considered by those responsible for designing and implementing meaningful public- and patient-involvement processes. Highlights: Australian processes do not meet the information needs of Advisory Committees. Nor do they accommodate patient organisation views, e.g. on illness experiences. Health policy-making processes need to account for stakeholders' power asymmetry. They also need to account for contrasting conceptions of evidence. Conceptions of evidence differ among patient organisations and Advisory Committees.